The Effect of Snake and Ladder Education Games on Knowledge of Sexual Violence Prevention in Children at Sdn 12 Meulaboh - Apriani, Fitri; Aulia, Yulfa; Satria, Orita; Nasution, Nurromsyah (Institute Of Computer Science (IOCS), 2025)
Background: Sex education aimed at preventing sexual violence in early childhood is often considered taboo within society, contributing to vulnerability of children to sexual violence. Thus, introducing and teaching sexuality, protect themselves, and respond appropriatly if they encounter sexual crimes. One method of delivering sex education is through educational games, such as snakes and ladders. Objective: To examine the impact of snake and ladder educational game on children’s knowledge of sexual violence prevention at SDN 12 Meulaboh. Method: this quasi experimental study employed a one group pretest and post test design, involving 58 participants selected through proportional stratified random sampling. The study was conducted from July 30 to August 14, 2024. Results: The wilcoxon test results indicated a significant improvement in children’s knowledge of sexual violence prevention following the snake and ladder educational intervention with p-value of 0.00 (p-value < 0.05), indicating the rejection of the null hypothesis (H0) and acceptence of the alternative hypothesis (Ha), with a z-score of -5.615. Conclusion: education through the snakes and ladders game is effective in increasing children’s knowledge of sexual violence prevention. Suggestion: it is necessary to carry out preventive efforts that are comprehensive, intensive and sustainable by parents, teachers, educational institutions and health workers to solve the problem and reduce the risk of sexual violence as well as guarantee the freedom for children to develop their abilities as the future generation.